Big infrastructure and/as flexibility: The Sites Reservoir story - RANDLE, Sarah Priscilla (Institutional Knowledge at Singapore Management University, 2024)
If constructed as planned, the Sites Reservoir Project will add roughly 1.85 billion m3 (1.5 million acre-feet) of storage capacity to California's water system. Per project proponents, however, the reservoir complex should be understood as infrastructure that would not only increase available water supply but also provide the state's water network with an infusion of a vital systemic quality: flexibility. This article considers such discourses of flexibility through a case study of the Sites project, grounded in analysis of planning documents, government, think tank, and NGO reports, and media coverage from outlets across California. The resulting account shows how the ideal of the flexible system orients efforts to adapt the California water network to the heightened forms of hydrological variability associated with climate change. The analysis traces the emergence of the notion of a "flexibility crisis" plaguing the state's water network and elaborates the temporalities and spatialities characteristic of the systemic flexibility that Sites is understood to enhance. The project of increasing the water network's flexibility through the construction of new large-scale storage infrastructures like Sites is shown to be an undertaking that serves to sustain of many of the system's established (and notably inflexible) consumptive arrangements. The case thus demonstrates the importance of attending to how material properties like flexibility – commonly glossed as desirable system-scale qualities – come to be unevenly spatialized within infrastructural networks and across landscapes.